Level of Familiarisation and Practical Use of Translation Tools by Translation Students - Sazdovska Pigulovska, Milena (Institute of English Studies, University of Wrocław, Poland, 2018)
Due to the fact that we live in the digital age, it is understandable that translation tools and technology are increasingly becoming an important area of research studies. Translators use a number of translation tools, such as terminology management software, printed and electronic dictionaries and glossaries, multilingual online terminological databases, terminology extraction tools, social networking tools, etc. In fact, translation tools are any tools and resources used by translators in the translation process whether they are in electronic, digital or printed format. Considering that translation is an energy-consuming and time-consuming process, which requires translation students to be meticulous about details, facts, terminology and transfer of meaning, students often look for shortcuts in the translation process, thereby disregarding the importance of research and use of various translation tools that contribute to high quality translations. The purpose of this paper is to analyse student practices in the translation classroom and their familiarisation with the most commonly used and useful translation tools. Based on the results of the conducted survey research, specific recommendations can be made about which translator’s competences and skills need improvement and further development. Furthermore, the paper strives to find practical application of the research results, aimed at improving applied practices in the translation classroom and the quality of students’ translations.
Keywords: Translation tools, translator training, survey, CAT tools, terminology database